O perfil do professor coordenador de laboratório de informática: a práxis na rede pública municipal de Juazeiro-BA - Silva, Girlene Feitosa da (2012)
This research aims to study the integration of information and communication technologies in teaching practice, aiming to investigate the profile of the teacher computer lab coordinator through the use of educational technology in public schools in Juazeiro, Bahia. The methodological procedure includes the exploratory study and has qualitative and quantitative approach. Data collection involves all head teachers in the laboratories of crowded public schools and the urban center of the country in 2010. The data collection instruments were used: document analysis and questionnaire available on Google docs and interview. The result revealed the evolution of technology and growing presence in public schools, and the desire in the voice of the survey, to innovate their practices. Their answers show that the practice can bring significant contributions and continuing education of teachers is a relevant factor, and could possibly promote the continuous change in doing teaching that necessarily must be shared among members and agent learning from the reflections that emerge collectively integration of practice and experiences in their teaching context and technology